The Investigation of Prostitution Service Providers through Social Media Information and Electronic Transactions - Hermawan Hermawan; Widayati Widayati; Peni Rinda Listyawati (Universitas Islam Sultan Agung, 2022)
The purpose of this research is to study and obstacles analysis and solutions in the process of investigating prostitution service providers through information media and electronic transactions. The specification of this research is the normative juridical method. The results of this study indicate that the investigation process carried out by the Cirebon City Resort Police in tackling the crime of online prostitution, investigators carried out several internal stages, including through the investigation process by disguise and trapping the perpetrators. And the obstacles experienced by the Cirebon City Police in the investigation process include collecting sufficient evidence and determining suspects. This is because there are no special rules regarding the investigation of online prostitution, so that investigators conduct undercover investigations as stipulated in the National Police Chief Regulation Number 6 of 2019 concerning Criminal Investigations, then the diversity of laws governing online prostitution, perpetrators falsify real identity, and unprofessional human resources in dealing with cases related to cybercrime. And the solution is the government should implementing truly the Act No. 11 of 2008 concerning Information and Electronic Transactions jo Act No. 19 of 2016 concerning Amendments to Act No. 11 of 2008 concerning Information and Electronic Transactions, Act No. 21 of 2007 concerning Eradication of the Crime of Trafficking in Persons, and Act No. 23 of 2002 concerning Child Protection.